The role of the school leadership in developing mathematics teachers professionally, its obstacles, and female teachers’ proposals for development in Makkah - Alsarwani, Seham Meshal (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the role of school leadership in professionally developing mathematics teachers in Makkah region, specifically in the fields of teaching methods and classroom management. And revealing the obstacles to professional development for them in preparation for developing the proposed solutions to overcome them, and to achieve the objectives of the study, the researcher adopted the descriptive survey approach, and the tool consisted of a ready-made questionnaire from the study of Al-Qahtani (2018) distributed to a sample of 154 mathematics teachers in Makkah. The results showed the following: The overall role of the school leadership in developing mathematics teachers in the Makkah region professionally has achieved a high rating at the level of the four main axes. The proposed solutions axis to activate the school leadership role in the professional development of female teachers got the highest average (4.28 out of 5) and approval score (very high), the teaching methods axis got an overall average ((4.07 with a high) rating, and the classroom management axis got an average (4.1) Finally, the axis of professional development obstacles got an average (3.75) with a rating of (high). Based on the results, the researcher presented a set of recommendations and proposals to activate the role of school leaders in developing the performance of mathematics teachers in Makkah and the whole Kingdom.